Nomenclatural notes in Brazilian Ternstroemia (Pentaphylacaceae) - Vieira, Jaqueline Alves [UNESP] (2021)
During the elaboration of the taxonomic revision for Pentaphylacaceae of Brazil, we detected five species (i.e., Ternstroemia alnifolia, T. brasiliensis, T. candolleana, T. cuneifolia and T. dentata) and a variety (i.e., T. candolleana var. angustifolia) in need of lectotypification. Furthermore, we provided the synonyms of the above mentioned species and identified five inadvertent lectotypifications performed by Kobuski, for which we provide a second-step lectotypification, resulting in the typification of 13 names of Ternstroemia from Brazil. Additionally, T. borbensis was reduce to a synonym of T. dentata.